2021
DOI: 10.1371/journal.pone.0256915
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative exploration of young people’s experiences of attempted suicide in the context of alcohol and substance use

Abstract: The aim of this study was to explore young people’s experiences of the role and the processes underpinning the use of alcohol and/or other substances in attempts to end their life. Seven young people, aged 16–25 years old, were interviewed using in-depth, semi-structured interviews. Interpretative Phenomenological Analysis was used to analyse these interviews and develop an understanding of how young people understand their attempted suicide in the context of alcohol and/or other substance use. The analysis id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Guest etal [11] UK poor life circumstances Bazrafshanetal [15] Iranian [20] America Hollidayetal [21] America/2015 trying to convert Dardasetal [22] Arabian Sukhawahaetal [23] Thailand /2016 Orrietal [25] Italy Aggarwal etal [10] Yes Yes Yes Yes Yes No No Yes Yes Yes B…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Guest etal [11] UK poor life circumstances Bazrafshanetal [15] Iranian [20] America Hollidayetal [21] America/2015 trying to convert Dardasetal [22] Arabian Sukhawahaetal [23] Thailand /2016 Orrietal [25] Italy Aggarwal etal [10] Yes Yes Yes Yes Yes No No Yes Yes Yes B…”
Section: Resultsmentioning
confidence: 99%
“…Guest etal [11] Yes Yes Yes Yes Yes Yes No Yes Yes Yes B Keyvanar etal [12] Yes Yes Yes Yes Yes Yes Yes Yes Yes Yes A Ye Minghui etal [13] Yes Yes Yes Yes Yes No No Yes Yes Yes B Shilubane etal [14] Yes Yes Yes Yes Yes Unclear Yes Yes Yes Yes B…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A second study aim was to conduct a qualitative narrative analysis to determine pathways through which substance use played a role in suicide attempts. Previous studies using qualitative analysis have broadly identified themes of common stressors, emotion dysregulation, and coping strategies, as well as heterogeneity in the degree of planning (Guest et al., 2021; Skopp et al., 2019). Recently, researchers employed content analysis to examine warning signs present in the attempt narratives of adults with substance use problems and identified a range of cognitive, behavioral, emotional, and social cues associated with acute risk (Conner et al., 2022).…”
Section: Introductionmentioning
confidence: 99%